Improving productivity in New Zealand's economy - Barker, Andrew (OECD Economics Department Working Papers, 2017)
New Zealand ranks highly on most indicators of well-being, but incomes are below the OECD average due to low labour productivity. Low labour productivity is only partly explained by the industry composition of the NZ economy and is primarily a consequence of sustained low multi-factor productivity growth within industries, as well as weak investment. Economic geography is an important factor in New Zealand's poor productivity performance, as the small size and remoteness of the economy diminish its access to global markets, the scale and efficiency of domestic businesses, the level of competition, and the ability to benefit from innovation at the global frontier. Policy and institutions are generally supportive of productivity growth, but there are a number of areas where there is scope for reforms that would help offset the country's geographical disadvantages and improve the welfare of New Zealanders over the coming decades. This includes promoting international connections, removing barriers to fixed capital investment (including taxation), accessing benefits from agglomeration by improving urban planning and infrastructure provision, enhancing competition and increasing investment in innovation and intangibles. This Working Paper relates to the 2017 OECD Economic Survey of New Zealand (www.oecd.org/eco/surveys/economic-survey-new-zealand.htm)